Three AtCesA6‐like members enhance biomass production by distinctively promoting cell growth in Arabidopsis. Issue 5 (23rd October 2017) - Hu, Huizhen; Zhang, Ran; Feng, Shengqiu; Wang, Youmei; Wang, Yanting; Fan, Chunfen; Li, Ying; Liu, Zengyu; Schneider, René; Xia, Tao; Ding, Shi‐You; Persson, Staffan; et al.
Summary: Cellulose is an abundant biopolymer and a prominent constituent of plant cell walls. Cellulose is also a central component to plant morphogenesis and contributes the bulk of a plant's biomass. While cellulose synthase ( CesA ) genes were identified over two decades ago, genetic manipulation of this family to enhance cellulose production has remained difficult. In this study, we show that increasing the expression levels of the three primary cell wall AtCesA6 ‐like genes ( AtCesA2, AtCesA5, AtCesA6 ), but not AtCesA3, AtCesA9 or secondary cell wall AtCesA7, can promote the expression of major primary wall CesA genes to accelerate primary wall CesA complex (cellulose synthase complexes, CSCs) particle movement for acquiring long microfibrils and consequently increasing cellulose production in Arabidopsis transgenic lines, as compared with wild‐type. The overexpression transgenic lines displayed changes in expression of genes related to cell growth and proliferation, perhaps explaining the enhanced growth of the transgenic seedlings. Notably, overexpression of the three AtCesA6 ‐like genes also enhanced secondary cell wall deposition that led to improved mechanical strength and higher biomass production in transgenic mature plants. Hence, we propose that overexpression of certain AtCesA genes can provide a biotechnological approach to increase cellulose synthesis and biomass accumulation in transgenic plants.